Strategic organizational support for stress and burnout: insights from rural teachers' stress profiles - Fan, Xi; Fang, Jianwei (Frontiers in Psychology, 2025)
IntroductionThis study investigated the profiles of perceived stress among rural teachers in China and examined their associations with occupational burnout and organizational support.MethodsA random online survey of 6,105 rural teachers was conducted, yielding 6,000 valid responses. Standardized scales were used to assess perceived stress, teacher burnout, and organizational support. Latent Profile Analysis was applied to identify distinct stress profiles.ResultsFour stress profiles emerged: High-Stress, Challenge, Balance, and Relaxed. Teachers in the High-Stress and Challenge groups reported higher levels of burnout and lower organizational support, while those in the Balance and Relaxed groups reported lower stress and burnout and higher organizational support. Demographic factors such as gender, age, marital status, and education significantly influenced stress profile membership.DiscussionThese findings highlight the heterogeneity of stress experiences among rural teachers and suggest the need for tailored interventions. Strategies such as workload reduction, psychological support, mindfulness training, mentoring, and enhanced organizational support are recommended to promote teacher well-being and support sustainable rural education.